Wallace Stevens : d’une version officieuse de la philosophie - Axel Nesme (Transatlantica)
This paper aims to show that Wallace Stevens’ “unofficial view of being” does not simply convey a sense of the world as it is in the perfect coincidence of imagination and reality. After exploring the connection between Heideggerian ontology and Stevens’ poetry “in times of need”, this paper examines the originating function of Stevens’ poems in light of Agamben’s theorization of deixis and voice, and of the specific role assigned to the syllable. Following Lacoue-Labarthe, I conclude with a discussion of Stevens’ poetry as experience concomittant with the withdrawal of being.